2017
DOI: 10.1108/ijmpb-07-2016-0057
|View full text |Cite
|
Sign up to set email alerts
|

Is there only one way of project management theorizing, or are there multiple sector-specific project management domains?

Abstract: Is there only one way of project management theorizing, or are there multiple sector-specific project management domains? Title of the paper: Is there only one way of project management theorizing, or are there multiple sector-specific project management domains?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 131 publications
0
5
0
Order By: Relevance
“…On the basis of obtaining information sharing, it writes smart contracts for the warehousing and shipping process. It utilizes the implementation functions of the Ethereum operating system and antimonopoly blockchain technology, so that not all network maintenance orders can be exchanged [ 10 ]. Decentralized fixed payment solves the problem of a shared project management mechanism.…”
Section: Information Sharing In Project Managementmentioning
confidence: 99%
“…On the basis of obtaining information sharing, it writes smart contracts for the warehousing and shipping process. It utilizes the implementation functions of the Ethereum operating system and antimonopoly blockchain technology, so that not all network maintenance orders can be exchanged [ 10 ]. Decentralized fixed payment solves the problem of a shared project management mechanism.…”
Section: Information Sharing In Project Managementmentioning
confidence: 99%
“…It extends the original triangle to comprise quantity, efficiency, and innovativeness and related three tensions. For completeness, it includes risk [42] and satisfaction [62] as additional criteria, the related arrows underlining that performance along the six dimensions affects the satisfaction with the project performance and that delay risk, cost overrun risk, quality risk [63] as well risks of low novelty and inefficient execution [64] affect project performance risk. 4.…”
Section: Discussionmentioning
confidence: 99%
“…Findings on Public-Private-Partnership initiatives influencing leadership performance is supported by several authors who opine that inter-organizational ties connecting project network actors have been demonstrated to differ significantly (Manning & Sydow, 2011). Inter-organizational interactions between project network participants, for example, may be defined by trust and commitment or serve as sources of risk in project networks (Eloranta, 2007;Artto et al, 2016). The findings on executive network with other organizations is supported by Davis & Cobb (2010) and Drees & Heugens (2013) who observed that Organizations engage in inter-organizational arrangements to cope with interdependencies, strengthen their legitimacy and restore some degree of control or autonomy over their environments Collaborations with other institutions.…”
Section: Descriptive Statistics Of the Relationship Between Inter-org...mentioning
confidence: 95%